Gender Differences in Environmental Sensitivity among Primary School Students - Sharad Sinha,; Seema Taneja, (INDIAN EDUCATIONAL REVIEW, 2025)
Environmental sensitivity is a significant objective of environment education to create an emotional empathy and bonding with environment so as to enhance environmental responsible behaviour. The purpose of this investigation was to study the environmental sensitivity of primary school students in relation to their gender and locus of control. The sample comprised 400 primary school students of Rohtak. 200 students were with external locus of control (123 boys and 77 girls) and 200 students with internal locus of control (119 boys and 81 girls).The tools employed were environmental sensitivity scale (developed by authors) and locus of control by Dr. Roma Pal (1982). Mean, S.D., and ANOVA were used to analyse the data.